Seismic steel jacketing of rectangular RC bridge columns for the mitigation of lap-splice failures. - Lin, Min-Lang (Earthquake engineering & structural dynamics.)
This paper investigated the use of external steel jacketing for seismic retrofit of non-ductile reinforced concrete (RC) bridge columns to prevent lap-splice failure. Three 1/2.5 scale specimens were tested under cyclic loads. The effectiveness of two types of steel jackets for improving the ductility and strength of specimens using inadequate transverse reinforcing and lap splice details were examined. An octagonal steel jacketing scheme for the seismic retrofitting of rectangular RC bridge columns was proposed. In addition, the methods for seismic retrofitting rectangular columns using elliptical steel jacketing were also critically tested. The test results indicated that the octagonal steel jackets can effectively provide confinement thereby mitigating failures as a result of inadequate transverse reinforcing and inadequate lap splices. Tests also confirmed that the ductility performance and the energy dissipation capacity of the specimens can be significantly improved by the octagonal steel jacket.